2003
DOI: 10.1073/pnas.1837812100
|View full text |Cite
|
Sign up to set email alerts
|

HILS1 is a spermatid-specific linker histone H1-like protein implicated in chromatin remodeling during mammalian spermiogenesis

Abstract: Chromatin remodeling is a major event that occurs during mammalian spermiogenesis, the process of spermatid maturation into spermatozoa. Nuclear condensation during spermiogenesis is accomplished by replacing somatic histones (linker histone H1 and core histones) and the testis-specific linker histone, H1t, with transition proteins and protamines. It has long been thought that H1t is the only testis-specific linker histone, and that all linker histones are replaced by transition proteins, and subsequently by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
137
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(146 citation statements)
references
References 42 publications
6
137
0
3
Order By: Relevance
“…However, variants of H2A such as H2AL1/2, H2A.Bbd, or of H1, such as H1t2 and Hils1, are specifically incorporated during the histone-to-protamine exchange in round/elongating spermatids [70], [71], [72], [73]. While H2AL1/2 mark pericentric heterochromatin during spermatogenesis, they are quickly displaced from paternal heterochromatin after fertilization [74], potentially restricting a functional role in paternal inheritance.…”
Section: Global Chromatin Remodeling During Spermiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…However, variants of H2A such as H2AL1/2, H2A.Bbd, or of H1, such as H1t2 and Hils1, are specifically incorporated during the histone-to-protamine exchange in round/elongating spermatids [70], [71], [72], [73]. While H2AL1/2 mark pericentric heterochromatin during spermatogenesis, they are quickly displaced from paternal heterochromatin after fertilization [74], potentially restricting a functional role in paternal inheritance.…”
Section: Global Chromatin Remodeling During Spermiogenesismentioning
confidence: 99%
“…Recently, another H2A variant, H2A.Lap1 has been shown to be loaded onto the X chromosome and autosomes in round spermatids and suggested to have a role in transcription of repressed genes [75]. Among testis-specific H1 variants, it was shown that Hils1 localizes to the same sites as Tnp2 and Prm1 [73], while deficiency for H1t2 was found to result in reduced sperm mobility and condensation defects [72].…”
Section: Global Chromatin Remodeling During Spermiogenesismentioning
confidence: 99%
“…The amount of functional information available for these rapidly evolving genes varies. Some genes have known roles in sperm-egg interaction (Acr, Howes et al 2001;Spa17, Richardson et al 1994;Spag8, Cheng et al 2007) or spermatogenesis (Hils1, Yan et al 2003). Another set of genes has inferred function on the basis of domain homology; a wide variety of functions are represented including receptor activity, DNA binding, and protein binding.…”
Section: 0001)mentioning
confidence: 99%
“…In spermatogonia and preleptotene spermatocytes, the linker histones H1a and H1b are expressed (6). When cells enter the meiotic prophase, somatic histones are partially replaced by testis-specific core histone variants, including TH2B, TH2A, and tH3 (6 -13) as well as by linker histone variants H1t (14), H1t2 (15), and HILS1 (16).…”
mentioning
confidence: 99%